2022
DOI: 10.1128/spectrum.01483-21
|View full text |Cite
|
Sign up to set email alerts
|

PM10 and Other Climatic Variables Are Important Predictors of Seasonal Variability of Coccidioidomycosis in Arizona

Abstract: The inhalation of environmental infectious propagules from the fungal pathogens Coccidioides immitis and Coccidioides posadasii by susceptible mammals can result in coccidioidomycosis (Valley fever). Arizona is known to be a region where the pathogen is hyperendemic, and reported cases are increasing throughout the western United States. Coccidioides spp. are naturally occurring fungi in arid soils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…Statistical modelling has been applied to investigate the changes in Valley fever incidence over time with changes in weather data. Only a weak correlation between weather data could be documented for Kern County in California [ 30 ], compared to areas in Arizona where a stronger correlation was found [ 31 ] using a different statistical model.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical modelling has been applied to investigate the changes in Valley fever incidence over time with changes in weather data. Only a weak correlation between weather data could be documented for Kern County in California [ 30 ], compared to areas in Arizona where a stronger correlation was found [ 31 ] using a different statistical model.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of statistical analysis, this study confirmed that PM 2.5 exposure over a period of one month affects invasive aspergillosis. Kollath et al (2022) found a significant association of average PM 10 with Valley fever (coccidioidomycosis), which is caused by Coccidioides spp . PM 10 had the most potent effect in the winter months, leading to increased infections two months after an increase in PM 10 .…”
Section: Infectious Aerosols and Particulatesmentioning
confidence: 99%
“…The time difference between the outbreak of fungal disease and the increase in airborne PM concentration tends to be longer than other microorganisms. , , The time taken from the time of initial exposure to the fungus to the onset of the disease varies depending on the patient, and the degree of exposure and the activity of the fungus in the air may also differ. In particular, since most fungal diseases, including invasive aspergillosis and coccidioidomycosis, usually occur in individuals with weakened immune systems, the infections are highly dependent on the condition of the patient. ,, The majority of acute respiratory diseases caused by pathogenic fungal infection show incidences with a time lag of one to 2 weeks after air pollution .…”
Section: Infectious Aerosols and Particulatesmentioning
confidence: 99%
“…These effects may be amplified after droughts; incidence in California declined during the 2007–2009 and 2012–2015 droughts but increased markedly in the following two years [ 23 ]. Particulate matter of size less than 10 µm (PM10) is also thought to impact coccidioidomycosis incidence, and PM10 concentration rose by 12% in the Southwest and 29% in the West from 2010–2020 [ 30 , 32 , 33 ].…”
Section: Epidemiologymentioning
confidence: 99%